Pro-Environmental Behavior Model among University Students - Hetti Rahmawati; Fonny Dameaty Hutagalung; Yudi Tri Harsono; Nur Rohmah Hidayatul Qoyyimah (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Environmental behavior is essential for maintaining environmental quality and human life. According to the rational perspective from Theory of Planned Behavior (TPB), belief, personal norm, and perceived behavioral control (PBC) affect actions through behavioral intention. In the past two decades, TPB has become the most extensively discussed concept in explaining pro-environmental behavior (PEB) but still needs re-examination in the Indonesian context. Therefore, this research aimed to investigate how subjective norm (SN), attitude (ATT) towards PEB, and PBC influenced PEB through pro-environmental behavior intention (PEBI). An explanatory quantitative method was used including 264 students from Malang State University with the data analysis conducted and structural equation modeling path analysis. The results showed that attitude, SN, and PBC significantly and positively influenced PEB, primarily through behavior intention.